A Novel Multidrug Resistant, Non-Tn4401 Genetic Element-Bearing, Strain of Klebsiella pneumoniae Isolated From an Urban Lake With Drinking and Recreational Water Reuse - Janssen, Luis; de Almeida, Felipe Marques; Damasceno, Thais Amanda Silva; Baptista, Rodrigo de Paula; Pappas, Georgios Joannis; de Campos, Tatiana Amabile; Martins, Vicente de Paulo (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is an increasing and urgent issue for human health worldwide, as it leads to the reduction of available antibiotics to treat bacterial infections, in turn increasing hospital stays and lethality. Therefore, the study and genomic surveillance of bacterial carriers of resistance in and outside of clinical settings is of utter importance. A colony of multidrug resistant (MDR) bacteria identified as Klebsiella spp., by 16S rDNA amplicon sequencing, has been isolated from an urban lake in Brazil, during a drug-degrading bacterial prospection. Genomic analyses revealed the bacteria as K. pneumoniae species. Furthermore, the in silico Multilocus Sequence Typing (MLST) identified the genome as a new sequence type, ST5236. The search for antimicrobial resistance genes (ARGs) detected the presence of genes against beta-lactams, fosfomycin, acriflavine and efflux pumps, as well as genes for heavy metal resistance. Of particular note, an extended-expectrum betalactamase gene (blaCTX-M-15) has been detected in close proximity to siphoviridae genes, while a carbapenemase gene (KPC-2) has been found in an extrachromosomal contig, within a novel non-Tn4401-element (NTEKPC). An extrachromossomal contig found in the V3 isolate is identical to a contig of a K.pneumoniae isolate from a nearby hospital, which indicates a putative gene flow from the hospital network into Paranoá lake. The discovery of a MDR isolate in this lake is worrisome, as the region has recently undergone periods of water scarcity causing the lake, which receives treated wastewater effluent, and is already used for recreational purposes, to be used as an environmental buffer for drinking water reuse. Altogether, our results indicate an underrepresentation of environmental K. pneumoniae among available genomes, which may hamper the understanding of the population dynamics of the species in the environment and its consequences in the spread of ARGs and virulence genes.